Effect of Se content on the oxygen evolution reaction activity and capacitive performance of MoSe2 nanoflakes. (20th April 2022) - Upadhyay, Sanjay; Pandey, O.P.
Highlights: MoSe2 : A highly efficient electrocatalyst for oxygen evolution reaction. Synthesis of MoSe2 nanoflakes through a facile solid-solid reaction method. Effect of Se content on OER activity of MoSe2 nanoflakes. MoSe2 showed high OER performance with long-term cyclic stability up to 5000 CV cycles. Abstract: In this work, a facile and cost-effective method is proposed to synthesize ultrathin MoSe2 nanoflakes. To get high purity MoSe2 nanoflakes, the reaction parameters are optimized. The TEM and Raman analysis confirmed the formation of few-layered MoSe2 nanoflakes consisting of 2 to 3 layers. The influence of Se content on the OER and capacitive performance of MoSe2 are studied in detail. The catalyst with optimal electrochemical performance (MS1.8) shows outstanding OER activity and capacitive performance. It requires a low overpotential of only 320 mV to reach a current density of 10 mA cm −2 with a low Tafel slope of 45.3 mV dec −1 . Also, it exhibited a specific capacity of 25 mAh g −1 at a current density of 1 A g −1 . The excellent OER activity of the MoSe2 nanoflakes can be attributed to the few-layered structure, which provides a high electrochemical surface area. Moreover, the prepared MoSe2 nanoflakes show excellent cyclic stability up to 5000 CV cycles. Our findings indicate that the amount of Se in MoSe2 plays a significant role in achieving maximum electrochemical performance from MoSe2 . The method used in this study may provide a low-cost and simple technique to synthesize non-noble MoSe2 for a wide-scale application. Graphical abstract: Image, graphical abstract